APPLICATION OF CALCULATION METHODS MULTI ATRIBUTTE UTILITY THEORY (MAUT) IN SELECTION OF YARN SUPPLIER - Susliansyah Susliansyah; Yahdi Kusnadi; Heny Sumarno; Hendro Priyono; Linda Maulida (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2021)
The main objective of the yarn supplier selection process is to determine suppliers who have efficiency in meeting the company's needs consistently and minimize risks related to the procurement of yarn and components needed. In solving problems in supplier selection using the Multi Attribute Utility Theory (MAUT) method which consists of calculating matrix normalization and attribute normalization. The results obtained in this study are to find out the best supplier from other suppliers, namely GSM suppliers with a value of 0.87.